La (dés)illusion communautaire. De l’ambivalence de la notion de « communauté » en Amazonie brésilienne - Émilie Stoll; Ricardo Theophilo Folhes (Journal de la Société des Américanistes)
In the Brazilian Amazon, the formation of rural « communities » was largely driven by the Catholic Church, and later strengthened by several external institutional actors. Now regarded as the political unit by external actors, it is the privileged interlocutor of many public policies concerned with land tenure and the redistribution of resources. In this article, using the case study of a set of rural communities along the Arapiuns River, in the state of Pará (Brazil), we show the dynamics driven in the genesis of communities’ formation and later in the deliverance of land records by the State, their nesting with local practices of land use and transfer. Social organization based on « residential sibling groups », and mechanisms of exclusion necessary to their reproduction, have found their limits in a legal structure seen as a cyclical confinement. Recent conflicts between residential groups and within families must be understood in the light of a broader crisis of representation and identity of the community.